PENGARUH PENGGUNAAN GROUNDING PADA KWH METER PRABAYAR - Moh. Wahyu Aminullah; Muhni Pamuji; Yuslan Basir (Universitas Tarumanagara, 2022)
The grounding system must be connected to every electrical panel of the building so that electrical installations, equipment, and people in the building can avoid the danger of overcurrent or voltage. In fact, the installation of grounding on prepaid kWh meters, especially in residential areas, is partially grounded because of the reason that errors often occur. This research was conducted when the prepaid kWh meter used grounding, kWh without using grounding, and kWh using grounding combined to Neutral with a different voltage source. The results of the study with three different test methods show that there is a difference in Power (W) and information on the Prepaid kWh Meter when testing the voltage varying from 270 V to TRIP at a voltage below 80 V. The power when testing using grounding is more maximal at a voltage of 220 -270V. when the voltage drops, testing using grounding is better because at a voltage of 140V there is already a warning sign in the form of a palm image on the prepaid kWh meter. Whereas in the test without using grounding, the warning appears at a voltage of 110V. The calculation of usage error at 220V shows that the smallest prepaid kWh meter error is using grounding of 1.063%. Meanwhile, the prepaid kWh meter error without grounding is 3.76%, and using grounding connected to neutral is 35.38%. Testing and calculating the prepaid kWh meter is very good when it is grounded. Starting from calculating small errors to maintaining losses from leakage currents in home electrical equipment and installations. ABSTRAK:Sistem grounding harus terkoneksi pada setiap panel listrik bangunan gedung agar instalasi listrik,peralatan, dan manusia yang berada pada bangunan tersebut dapat terhindar dari bahaya arus atau tegangan lebih. Kenyataannya pemasangan grounding pada kWh meter prabayar terutama di area perumahan sebagian tidak dipasang grounding dengan alasan sering terjadi error. Penelitian ini dilakukan pada saat kWh meter prabayar menggunakan grounding, kWh tanpa menggunakan grounding, dan kWh menggunakan grounding di gabung ke Netral dengan sumber tegangan yang berbeda. Hasil Penelitian dengan tiga metode pengujian yang berbeda menunjukkan bahwa terdapat perbedaan Daya (W) dan keterangan pada kWh Meter Prabayar saat dilakukan pengujian tegangan yang bervariasi dari 270 V hingga TRIP pada tegangan dibawah 80 V. Daya pada saat pengujian menggunakan grounding lebih maximal pada tegangan 220-270V. ketika tegangan turun, pengujian menggunakan grounding lebih baik dikarenakan pada tegangan 140V sudah ada tanda peringatan berupa gambar telapak tangan pada kWh meter prabayar. Sedangkan pada pengujian tanpa menggunakan grounding, maka peringatan tersebut muncul pada tegangan 110V. Perhitungan error pemakaian pada tegangan 220V menunjukkan error kWh meter prabayar terkecil adalah menggunakan grounding sebesar 1,063%. Sedangkan error kWh meter prabayar tanpa grounding sebesar 3,76%, dan menggunakan grounding disambung ke netral sebesar 35,38%. Pengujian dan perhitungan kWh meter prabayar sangat baik bila dipasang grounding. Mulai dari perhitungan error yang kecil hingga menjaga kerugian dari arus bocor pada peralatan maupun instalasi listrik rumah.